2017
DOI: 10.4314/njb.v33i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic diversity and phylogeographic structure of duck (<i>Anas platyrhynchos</i>) in Nigeria using mitochondrial DNA D-loop sequences

Abstract: In this study, the maternal genetic diversity and phylogenetic relationship of Nigerian duck populations were assessed. A total of 591 base pair fragment of the mitochondrial DNA (mtDNA) D-loop region of 87 indigenous ducks from two populations in Nigeria were analyzed. Seven haplotypes and 70 polymorphic sites were identified. The mean haplotypic and nucleotide diversity were found to be 0.381±0.058 and 0.315±0.155 respectively. The phylogeny revealed two divergent haplotype clades, suggesting two possible ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…In accord-ance, Purwantini et al (2013 b ) stated that local duck crossbreeding may have generated the high variability in the mtDNA D-loop region as seen in the Indonesian duck population. Further, high genetic diversity indicates that the population hasn't experienced either population expansion or selection, as well as human exploration activities in the particular area, thus the population still preserves its genetic uniqueness (Adebambo et al, 2017). On the contrary, the π value is denoted as low (Table 3).…”
Section: A Pla Tyrinc Ho S a C T A C A T A C C C A A C T C A A A C A C Tmentioning
confidence: 99%
“…In accord-ance, Purwantini et al (2013 b ) stated that local duck crossbreeding may have generated the high variability in the mtDNA D-loop region as seen in the Indonesian duck population. Further, high genetic diversity indicates that the population hasn't experienced either population expansion or selection, as well as human exploration activities in the particular area, thus the population still preserves its genetic uniqueness (Adebambo et al, 2017). On the contrary, the π value is denoted as low (Table 3).…”
Section: A Pla Tyrinc Ho S a C T A C A T A C C C A A C T C A A A C A C Tmentioning
confidence: 99%
“…Reports of recent studies by Adeola et al (2020;2022) revealed low genetic diversity between and within Nigerian Muscovy ducks. In another study, Adebambo et al (2017) equally reported a relatively high genetic diversity and differentiation among Nigerian ducks using the mitochondrial DNA (mtDNA) D-loop region. Likewise, Ogah et al (2017) equally discovered low genetic diversity in Nigerian Muscovy ducks using the mitochondrial D-Loop sequence while Sola-Ojo et al ( 2021) reported a wide genetic merger among Nigerian Muscovy ducks while using the nuclear DNA CYP2U1 gene.…”
Section: Molecular Characterisation Of Local Ducks In Nigeriamentioning
confidence: 99%